FINANCIAL CRISES BETWEEN THE POSTURAL ECONOMY THOUGHT AND THE THOUGHT OF THE ISLAMIC ECONOMY - Al-Momani, Mohammed (European Scientific Journal, ESJ, 2014)
This study aimed to identify the various financial crises by knowing their causes and effects and then figuring out the solutions to the crises which the postural economy posed. Therefore, this hassled to the claims by Islamic economics solutions, where by the researcher uses the descriptive method that describes the problem in question to achieve its objectives. This was attained through the study of documents, books and research related to the study to show the theoretical background of the financial crises. In the light of this, the researcher concluded on a number of important results that the postural economy is based on al gharar (buying something without knowing the result of the bargain, such as selling fish in the sea, birds in the air), and usury which is forbidden in the Islamic economy. In addition, Islamic religion forbids the abuse of people’s wealth unlawfully, but calls for all kinds of investment based on profits gained by the loss base.